Beyond aroma: A scoping review on the impact of chronic rhinosinusitis on retronasal olfaction - James, Joel; Palte, Ilan C.; Vilarello, Brandon J.; Axiotakis, Lucas G.; Jacobson, Patricia T.; Gudis, David A.; Overdevest, Jonathan B. (Frontiers in Allergy, 2022)
Background: Retronasal olfaction (RNO) refers to the perception of odorants inhaled through the mouth and carried through the nasopharynx to olfactory receptors within the olfactory cleft, enabling the perception of flavor. Although orthonasal olfactory dysfunction in chronic rhinosinusitis (CRS) has been widely described, the impact of CRS on RNO is less clear. In this study, we systematically review available literature to provide an update on RNO in the setting of CRS. Methods: We systematically searched PubMed, Ovid Embase, Web of Science, and the Cochrane Library for studies examining RNO in patients with documented CRS. The primary outcome of interest was objective psychophysical measurement of olfaction, including characterization of RNO. Results: We identified 404 unique references that underwent title and abstract review by two independent reviewers, with 52 articles undergoing full-text review, where 10 relevant studies underwent data extraction. Although outcome measures varied, all included studies demonstrated diminished RNO in patients with CRS. Of six studies evaluating the relationship between retronasal and orthonasal olfactory test scores in CRS patients two out of six (33%) demonstrated a correlation between both forms of olfaction and CRS, and two out of six studies (33%) found significantly lower orthonasal olfactory test scores compared to retronasal olfactory test scores. Two of three found significant improvement in RNO with treatment of underlying CRS. Of three studies examining patient reported outcome measures (PROMs) in CRS, two found significant associations between retronasal olfactory test scores and PROMs. Conclusions: Based on the current literature, CRS patients appear to have diminished RNO, which may be associated with orthonasal olfactory dysfunction and decreased quality of life in this population. Higher level of evidence studies are required to further elucidate these relationships and the impact of medical and surgical CRS management on RNO.